y" -5y' +4y=0 ;y(0)=1 and y' (0)=1 .
"y'' -5y' +4y=0 ; \\space \\space\\space \\space y(0)=1 \\space\\space \\space and \\space \\space\\space y' (0)=1 ."
Setup the auxilary equation
"\\lambda^2 - 5\\lambda +4 = 0 \\to \\lambda_1= 1 \\space \\space\\space \\space \\lambda_2=4"
The general solution is found by
Usually problem like these will have the answer in the form "C_1e^a+C_2e^b..." where a and b are the roots of the characteristic equation "e^{rt}"
y = "C_1e^{t} + C_2e^{4t}" "\\to C_1+C_2 = 1"
"y' = C_1e^t+4C_2e^{4t} \\to C_1+4C_2 = 1"
"C_1 = 1 \\space\\space\\space\\space C_2= 0"
The general solution is: "y = e^t"
Comments
Leave a comment